(3OjhGf GHf gJjeds - (3GdbGSe Hf Ydj Hf gJjed GdNRGYj Gdjefj GdeNdGaj,J (B656 (3g` s ((3YHOGdbGOQ Hf GdfGUQ Hf GdEeGe s)
(3ChdgG (B:s
(3dG JYGdL ef GdUHGHI OGA agh OGA CYjG GdWHjH OhGA s
(3BNQgG (B:s
(3hGdeOgT hGdeOgT GdSMGH Mjf HOG aj Qbe QGbeg Ch hTi hGTjg s
(3GdOjhGf oeQJH Ydi GdMQhas
(3hHBNQ GdfSNI edMb GdOjhGf hGdfSNI HgG HYV GdVHWs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B109s
Keywords: (3GdCOHs